Existence of density function for the running maximum of SDEs driven by nontruncated pure-jump Lévy processes - Nakagawa, Takuya; Suzuki, Ryoichi (Modern Stochastics: Theory and Applications, 2024)
The existence of density function of the running maximum of a stochastic differential equation (SDE) driven by a Brownian motion and a nontruncated pure-jump process is verified. This is proved by the existence of density function of the running maximum of the Wiener–Poisson functionals resulting from Bismut’s approach to the Malliavin calculus for jump processes.